2013
DOI: 10.1097/mib.0b013e31829080a8
|View full text |Cite
|
Sign up to set email alerts
|

Cause-Specific Mortality and 30-year Relative Survival of Crohnʼs Disease and Ulcerative Colitis

Abstract: In Australia, IBD patient survival is similar to the general population. In contrast to data from Europe and North America, survival in CD is not diminished in Australia. IBD caused direct mortality in 17%, especially as biliary and colorectal cancers are significant causes of death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 37 publications
3
33
0
Order By: Relevance
“…The overall pattern of our results is in agreement with our own previous findings when we reported a proportionate increase in mortality of 54% in all IBD patients 3 , the magnitude of the relative risk now reported is only slightly smaller despite the quite marked changes in therapy over this period 9,10 . Other studies have identified varying increased risks of death among IBD patients 3,4,[14][15][16][17][18] while other studies found no increase [19][20][21][22][23] Interestingly though neoplasia is classically a disease of the old, the proportion of deaths due to it in UC falls with age (though not with time since diagnosis). There were 19 deaths from lower gastrointestinal cancers in the first 5 years after the diagnosis of IBD, perhaps in keeping with the high hazard for death from this cause previously reported in the early years 4 .…”
Section: Discussionmentioning
confidence: 99%
“…The overall pattern of our results is in agreement with our own previous findings when we reported a proportionate increase in mortality of 54% in all IBD patients 3 , the magnitude of the relative risk now reported is only slightly smaller despite the quite marked changes in therapy over this period 9,10 . Other studies have identified varying increased risks of death among IBD patients 3,4,[14][15][16][17][18] while other studies found no increase [19][20][21][22][23] Interestingly though neoplasia is classically a disease of the old, the proportion of deaths due to it in UC falls with age (though not with time since diagnosis). There were 19 deaths from lower gastrointestinal cancers in the first 5 years after the diagnosis of IBD, perhaps in keeping with the high hazard for death from this cause previously reported in the early years 4 .…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been reported that mortality is similar or slightly higher in CD patients than in the general population [5][6][7][8][9][10][11][12][13][14]. However, most data are derived from population-based studies, which are considered not conducive to patient follow-up or detailed investigation of the causes of deaths, and there are very few, long-term, hospital-based studies with a large sample size [5,6,14,[21][22][23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…It is also known to frequently require intestinal resection due to the development of intestinal complications such as stenosis and fistula through repeated relapses or recurrences [1][2][3][4]. Although there are some reports of the long-term course of patients with this disease, there are very few reports related to their survival and cause of death; moreover, most previous reports are derived from population-based cohort studies, and there are very few, long-term, hospital-based, cohort studies with a long duration of follow-up and a large sample size [5][6][7][8][9][10][11][12][13][14]. In the present study, a database based on the medical records of CD patients at our hospital with the addition of information obtained from a questionnaire survey was created, and the long-term prognosis of CD patients was investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Given that IBD affects a young patient demographic with normal life expectancy [11], treatment decisions must be strategic, balancing drug potency, side effects and the likely duration of therapy [7]. The choice of therapy is best personalised, tailored to patient goals and treatment acceptability [12].…”
Section: Patient Factorsmentioning
confidence: 99%